Black snow : Curtis LeMay, the firebombing of Tokyo, and the road to the atomic bomb - Scott, James (James M.) (W. W. Norton & Company, 2022)
"Black Snow brilliantly vivifies the horrific reality of the most destructive air attack in history, against Tokyo on the night of March 9-10, 1945. James Scott deftly employs sharply etched portraits of individuals of all stations and nationalities to survey the global, technological, and moral backdrop of the cataclysm, including the searing experiences of Japanese trapped in a gigantic firestorm. This riveting account illuminates an historical moment of profound contemporary relevance." --Richard B. Frank, author of Tower of Skulls: A History of the Asia-Pacific War: July 1937-May 1942.